American lion : [compact disc, abridged] : Andrew Jackson in the White House - Meacham, Jon (Random House Audio, 2008)
Journalist and biographer Jon Meacham chronicles the complex and passionate life of Andrew Jackson, the man who shaped the modern presidency and founded the Democratic party.